How Corporate Social (Ir)Responsibility Influences Employees' Private Prosocial Behavior: An Experimental Study - Irmela Fritzi Koch-Bayram; Torsten Biemann (Journal of Business Ethics, 2024)
The micro-level corporate social responsibility (CSR) literature has broadly demonstrated the effects of CSR on employees' behavior but has mostly been limited to employees' behavior within the work domain. This business-centered focus overlooks the potential of organizations to change employees' private social and environmental behavior and thus to address grand societal challenges. Based on the social psychology literature on moral consistency and moral balancing, we conduct three experiments to investigate whether employees' private prosocial behavior is consistent with their organization's corporate social (ir)responsibility or whether employees aim to balance their private prosocial behavior, e.g., by compensating for their organization's CSR activities with a reduced willingness to contribute outside the work domain. Our results provide support for a consistency effect such that employers' environmental CSR activities increase employees' donations and willingness to volunteer outside work. Environmental corporate social irresponsibility activities, on the contrary, reduce employees' private donations and willingness to volunteer. We further find that the positive effects of environmental CSR are partly explained by the strengthening of employees' environmental self-identity. Our findings highlight that organizational activities have consequences for employees' moral behavior outside the work domain and thus have important implications for research and practice.
Keywords: 300; Corporate social responsibility; Corporate social irresponsibility; Employees; Moral consistency; Environmental self-identity